Studi Evaluatif Tentang Kesiapan Mengajar Mahasiswa Calon Guru Program Studi Pendidikan Ekonomi Universitas PGRI Mahadewa Indonesia Tahun Akademik 2020/2021 - Epong, Patrisia Graseila; Sudarsana, Ida Bagus Oka; Wirawan, I Dewa Gede Kresna; Naut, Astutika; Nasraya, Fabiola (Universitas Pendidikan Ganesha, 2022)
The purpose of this research is to improve and continue a program, especially PPL through a comprehensive and systematic evaluation of the planning and implementation of PPL to be able to see the strengths, weaknesses, opportunities, and threats in the learning process that takes place at the teacher education institution. This research was conducted at the Economic Education Study Program, Faculty of Teacher Training and Education (FKIP) Universitas PGRI Mahadewa Indonesia using 60 samples. Based on the analysis, it can be obtained suggestions, namely, Economics Education Study Program must maintain interest in being a teacher which is owned by students because it is included in the very good category regarding the profession of being a teacher. Efforts need to be made to eliminate the notion that the teaching profession has a heavy duty and only a small salary, showing the condition of honorary teachers who sometimes do not get the reward commensurate with their hard work. Teaching readiness of prospective teacher students to see the characteristics of students can support teaching and learning activities to be improved. The ability to design learning that is useful for students in everyday life still needs to be improved.